Professionals' perspectives on a market-inspired policy reform: A guiding light to the blind spots of measurement. (August 2017) - Korlén, Sara; Amer-Wåhlin, Isis; Lindgren, Peter; von Thiele Schwarz, Ulrica
Implementation of market-inspired competition and incentive models in health care is increasing worldwide, assumed to drive efficiency. However, the evidence for effects is mixed and unintended consequences have been reported. There is a need to better understand the practical consequences of such reforms. The aim of the present case study is to explore what consequences of a Swedish market-inspired patient choice reform professionals identify as relevant, and why. The study was designed as an explorative qualitative study in specialized orthopedics. Nineteen interviews were conducted with health care professionals at different providers. Data were analyzed using a hypo-deductive thematic approach. Consequences for the organization of care, patients, work environment, education and research were included in the professionals' analyses, covering both the perspective of their own organization and that of the health care system as a whole. In sum, the professionals provided multiple-level analyses that extended beyond the responsibilities of their own organization. Concluding, professionals are a valuable source of knowledge when evaluating policy reforms. Their analyses can contribute by covering a broad system perspective, serving as a guiding light to areas beyond the most obvious evaluation measures that should be included in more formal evaluations.